Preclinical immunological evaluation of an intradermal heterologous vaccine against SARS-CoV-2 variants. Issue 1 (31st December 2022) - Fan, Shengtao; Xiao, Kang; Li, Dandan; Zhao, Heng; Zhang, Jingjing; Yu, Li; Chang, Penglan; Zhu, Shuangli; Xu, Xingli; Liao, Yun; Ji, Tianjiao; Jiang, Guorun; et al.
ABSTRACT: The recent emergence of COVID-19 variants has necessitated the development of new vaccines that stimulate the formation of high levels of neutralizing antibodies against S antigen variants. A new strategy involves the intradermal administration of heterologous vaccines composed of one or two doses of inactivated vaccine and a booster dose with the mutated S1 protein (K-S). Such vaccines improve the immune efficacy by increasing the neutralizing antibody titers and promoting specific T cell responses against five variants of the RBD protein. A viral challenge test with the B.1.617.2 (Delta) variant confirmed that both administration schedules (i.e. "1 + 1" and "2 + 1") ensured protection against this strain. These results suggest that the aforementioned strategy is effective for protecting against new variants and enhances the anamnestic immune response in the immunized population.